The Hagia Photia Cemetery : II: The pottery - Davaras, Kōstēs (Prehistory monographs, 2012)
The publication of the Hagia Photia Cemetery is planned in three volumes. The first volume, which has already been published (Davaras and Betancourt 2004), presented the tomb groups and the architecture. The second volume about the excavation of the Hagia Photia cemetery focuses on the pottery. The third volume will present the obsidian, stone finds, metal objects, and other discoveries. The Early Minoan I tombs at Hagia Photia included the largest assemblage of vessels in Cycladic style known from Crete as well as vases from production workshops in Crete. The pottery is extremely important for several reasons, including the definition of the EM I ceramic styles that were being used as funerary offerings in this part of Crete, the establishment of the chronological synchronisms between Crete and the Cyclades, and information on the history of the Minoan pottery industry. When compared with other deposits from EM I Crete, the pottery helps to establish a better understanding of the ceramic development within the first Minoan time period